2018
DOI: 10.1111/cas.13754
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia‐induced slug promotes invasive behavior of prostate cancer cells by activating expression of ephrin‐B1

Abstract: Advanced solid tumors are exposed to hypoxic conditions over longer periods of time as they grow. Tumor hypoxia is a major factor that induces malignant progression, but most previous studies on tumor hypoxia were performed under short‐term hypoxia for up to 72 hours and few studies have focused on tumor response to chronic hypoxic conditions. Here we show a molecular mechanism by which chronic hypoxia promotes invasive behavior in prostate cancer cells. We found that an epithelial‐mesenchymal transition (EMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Conversely, they did not find any significant association between increase in expression of ESRP1/2 in prostate carcinoma and E-cadherin levels. It is possible that more evident sign of the activation of EMT may be visible in our assay after a longer period of incubation as reported by previously published evidence using the same cell lines in which EMT was analyzed after 48 or 72 h [54,55]. However, to be consistent with the invasion assay time frame, we analyzed cells 24 h after treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Conversely, they did not find any significant association between increase in expression of ESRP1/2 in prostate carcinoma and E-cadherin levels. It is possible that more evident sign of the activation of EMT may be visible in our assay after a longer period of incubation as reported by previously published evidence using the same cell lines in which EMT was analyzed after 48 or 72 h [54,55]. However, to be consistent with the invasion assay time frame, we analyzed cells 24 h after treatment.…”
Section: Discussionmentioning
confidence: 59%
“…However, to date, few studies have been focused on long-term hypoxia-promoting tumor metastasis. The limited studies related to long-term hypoxia of tumors reported that slug promoted metastasis of prostate cancer under chronic hypoxia (12); miR-191 induced by chronic hypoxia promoted cell migration in NSCLC (13). Due to the discovery more novel important functions of non-coding RNAs (ncRNAs) including miRNAs, LncRNAs, and circRNAs, participating in tumor progression, we pay special attention in the present work to the role of hypoxia microenvironment-related ncRNAs in GC.…”
Section: Introductionmentioning
confidence: 99%
“…For another important zinc-finger binding transcription factor Slug, HIF-1α was associated with its expression in head and neck squamous carcinoma, lung, and pancreatic cancer cells (33,64,66,67). Similar to Snail, Slug was also suggested to contain HRE in its promoter for direct interaction between HIF-1α and Slug (75).…”
Section: Hif-mediated Emtmentioning
confidence: 99%